PENINGKATAN HASIL BELAJAR FISIKA MELALUI PENERAPAN MODEL PEMBELAJARAN TUTOR SEBAYA SISWA SMAN 3 BENGKALIS - SURYANI SURYANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is classroom action research using a peer tutor learning model to improve physics learning outcomes. Peer tutor learning is a learning that utilizes classmates who have more ability to help their friends in carrying out an activity or understanding the concept of learning. The problem to be solved is the low physics learning outcomes of class XI MIA 1 in SMA 3 Bengkalis. This study consisted of three cycles, in each cycle consisting of four stages, namely Planning, Implementation, Observation and Reflection. This research involved 24 students which are consisting of 13 female students and 11 male students. In the pre-cycle process, the percentage of learning completeness was 29,17 %, then after learning the first cycle using the peer tutoring model there was an increase in the percentage of learning completeness to 54,17 %. In the second cycle, it succeeded in achieving the percentage of learning completeness of 70,83 %. The results showed that an increase in student learning outcomes along with the application of peer tutoring models. Thus, the results of the study indicate that the use of peer tutoring models can improve the physics learning outcomes of XI MIA 1 students in SMAN 3 Bengkalis. ABSTRAKPenelitian ini adalah penelitian tindakan kelas (PTK) dengan menerapkan model pembelajaran tutor sebaya untuk meningkatkan hasil belajar fisika. Pembelajaran tutor sebaya adalah pembelajaran yang memanfaatkan teman sekelas yang mempunyai kemampuan lebih untuk membantu temannya dalam melaksanakan suatu kegiatan atau memahami konsep pembelajaran. Masalah yang hendak dipecahkan adalah rendahnya hasil belajar fisika kelas XI MIA 1 di SMA Negeri 3 Bengkalis. Penelitian ini terdiri dari dua siklus, pada setiap siklus terdiri dari empat tahapan, yaitu Perencanaan, Pelaksanaan, Observasi dan Refleksi. Penelitian ini melibatkan 24 orang siswa kelas X1 MIA 1 SMA Negeri 3 Bengkalis yang terdiri dari 13 siswa perempuan dan 11 siswa laki-laki. Pada proses prasiklus, persentase ketuntasan belajar sebesar 29,17 %, kemudian setelah dilaksanakan pembelajaran siklus 1 dengan menggunakan model tutor sebaya ada peningkatan persentase ketuntasan belajar menjadi 54,17 %. Pada siklus 2 berhasil mencapai persentase ketuntasan belajar 70,83 %. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil belajar siswa seiring dengan diterapkannya model tutor sebaya. Dengan demikian, hasil penelitian menunjukkan penerapan model tutor sebaya dapat meningkatkan hasil belajar fisika siswa kelas XI MIA 1 SMA Negeri 3 Bengkalis.